Supplementary descriptions of Australian Rhinotorini (Diptera: Heteromyzidae) - Mcalpine, David K. (Zootaxa, 2013)
Additional material of rhinotorine flies (Diptera: family Heteromyzidae or Heleomyzidae) is studied, much of it collected by the late Donald H. Colless. A distinctive morphological feature of the antenna, present in a majority of genera of the tribe Rhinotorini, is briefly described. Keys are given to the Australasian genera of Rhinotorini and to the species of Cairn-simyia Malloch and Zentula McAlpine. Cairnsimyia englishae n. sp. (New South Wales), Cairnsimyia collessi n. sp. (Queensland), and Zentula tropica n. sp. (Queensland) are described.